The effects of prenatal exposure to alcohol and environmental tobacco smoke on risk for ADHD: A large population-based study. Issue 1 (30th January 2015) - Han, Ji-Youn; Kwon, Ho-Jang; Ha, Mina; Paik, Ki-Chung; Lim, Myung-Ho; Gyu Lee, Sang; Yoo, Seung-Jin; Kim, Eun-Jung
Abstract: Attention deficit hyperactivity disorder (ADHD) is caused by the interaction of genetic and environmental factors. The objective of this study was to examine the effects of prenatal exposure to alcohol and environmental tobacco smoke (ETS). Among the 30, 552 parents who responded to a survey, the answers of 19, 940 who replied to questions on prenatal exposure to ETS, alcohol consumption, and completed the DuPaul Rating Scale were analyzed. Results revealed that risk of ADHD significantly increased as a result of exposure to alcohol by 1.55 times (95% CI 1.33–1.82), maternal smoking during pregnancy by 2.64 times (95% CI 1.45–4.80), and paternal smoking during pregnancy by 1.17 times (95% CI 1.98–1.39). When the subjects whose mothers did not smoke during pregnancy were divided into 4 groups, the prevalence was 1.16 times higher (95% CI 1.02–1.33) in the group exposed to ETS but not alcohol, 1.19 times higher (95% CI 0.91–1.57) in the group exposed to alcohol but not ETS, and 1.58 times higher (95% CI 1.31–1.91) in the group exposed to ETS and alcohol. The differences between the groups were statistically significantly ( P <0.0001). This result shows that simultaneous exposure to ETS and alcohol during pregnancy increases the risk of ADHD. Highlights: The risk of ADHD was 1.55 times higher (95% CI 1.33–1.82) in children of mothers who consumed alcohol during pregnancy than in those whose mothers did not consume alcohol. If the mother smoked during pregnancy, the risk of ADHD was approximately 2.64 times higher (95% CI 1.45–4.80). When the subjects whose mothers did not smoke during pregnancy were divided into 4 groups, the prevalence was 1.58 times higher (95% CI 1.31–1.91) in the group exposed to ETS and alcohol.